Integrated 16S rRNA sequencing and metagenomics insights into microbial dysbiosis and distinct virulence factors in inflammatory bowel disease - Wang, Haijing; Wang, Yuanjun; Yang, Libin; Feng, Jiawen; Tian, Shou; Chen, Lingyan; Huang, Wei; Liu, Jia; Wang, Xiaojin (Frontiers in Microbiology, 2024)
Introduction The escalation of urbanization correlates with rising rates of inflammatory bowel disease (IBD), necessitating research into new etiological factors. This study aims to elucidate the gut microbiota profiles in IBD patients and compare them with healthy controls in a western city of China. Methods We conducted a multicenter case-control study from the end of 2020, using 16S rRNA gene sequencing (n = 36) and metagenomic sequencing (n = 12) to analyze the gut microbiota of newly diagnosed IBD patients, including those with Crohn's disease (CD) and ulcerative colitis (UC). Results Our results demonstrated a significant enrichment of the phylum Proteobacteria, particularly the genus Escherichia-Shigella, in CD patients. Conversely, the genus Enterococcus was markedly increased in UC patients. The core gut microbiota, such as the Christensenellaceae R-7 group, Fusicatenibacter, and Holdemanella, were primarily identified in healthy subjects. Additionally, significant interactions between the microbiome and virulence factors were observed. Discussion The findings suggest that oxidative stress may play a pivotal role in the pathology of IBD. This study contributes to the growing dialogue about the impact of gut microbiota on the development of IBD and its variations across different geographies, highlighting potential avenues for further research.